Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.4314/tjpr.v19i7.16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies of the anti-thrombotic effects of saffron and HongHua based on network pharmacology

Abstract: Purpose: To investigate the comparative anti-thrombotic effects of saffron and Honghua, and also to explore possible mechanisms in thrombosis based on network pharmacology. Methods: A network pharmacology model was used for bioactive components, targets and pathways for saffron and HongHua via Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP), PharmMapper, Genecard, Uniprot and KEGG databases. In animal experiments, 72 rats were randomly divided into 9 groups: norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
1
1
0
Order By: Relevance
“…In recent years, network pharmacology has been widely used in traditional Chinese medicine to investigate the potential therapeutic targets and pharmacological mechanisms in different diseases, however, very few studies have used network pharmacology to study the pharmacological effects of saffron. Consistent with our results, a comparative study of the anti-thrombotic effects of saffron and carthami flos based on network pharmacology indicated that CCT was the key bioactive ingredient of saffron ( 39 ). Two other studies on systems pharmacology of saffron emphasized the importance of CCT ( 40 , 41 ).…”
Section: Discussionsupporting
confidence: 90%
“…In recent years, network pharmacology has been widely used in traditional Chinese medicine to investigate the potential therapeutic targets and pharmacological mechanisms in different diseases, however, very few studies have used network pharmacology to study the pharmacological effects of saffron. Consistent with our results, a comparative study of the anti-thrombotic effects of saffron and carthami flos based on network pharmacology indicated that CCT was the key bioactive ingredient of saffron ( 39 ). Two other studies on systems pharmacology of saffron emphasized the importance of CCT ( 40 , 41 ).…”
Section: Discussionsupporting
confidence: 90%
“…The crocin biosynthesis pathway in C. sativus, from zeaxanthin to the crocins themselves, lies downstream of the methylerythritol phosphate (MEP) and mevalonate (MVA) pathways, which supply precursors and metabolites to the midstream carotenoid pathway, comprising GGPP to zeaxanthin (Figure 2) [14,[70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. Apart from the astaxanthin synthesis pathway, which is only present in a few specialized microalgae, most algal species in the taxon Chlorophyta share the majority of steps in the carotenoid biosynthesis pathway with higher plants [85].…”
Section: Biosynthesis Of Crocin In C Sativusmentioning
confidence: 99%